PENGARUH PEMANFAATAN GADGET DAN KEDISIPLINAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII - Mariani, Lidya Rizky; Haeruddin, Haeruddin; Asyril, Asyril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This ex post facto research aims to determine the effect of gadget usage (X_1) and learning discipline (X_2) on mathematics learning outcomes (Y) for class VIII students at SMP Negeri 4 Samarinda for the 2023/2024 academic year. In this study there are two independents variable, namely gadget usage and learning discipline and one dependent variable, namely students' mathematics learning outcomes. The population of this study were all students of class VIII SMP Negeri 4 Samarinda for the 2023/2024 academic year. Sampling using cluster random sampling technique and the sample used was 186 students. The instruments used include questionnaires on gadget usage and learning discipline as well as tests on mathematics learning outcomes. Data analysis in this study is descriptive statistics and inferential statistics, namely multiple linear regression analysis with a significance level of 5%. The descriptive analysis show that the average gadget usage in the medium category and the average learning discipline is in the medium category and the mathematics learning outcomes are in the low category. The results of inferential analysis using multiple linear regression analysis showed that the F test value showed a significance value of F (0.000), so rejecting H_0 meant that there was an effect of the use of gadgets and learning discipline on students' mathematics learning outcomes. The results of the analysis using the t test show that the significance value for the regression coefficient (gadget use) and significance value (learning discipline) is less than , namely 0,026<0,05 and 0,008<0,05, so reject H_0 means that the gadget use variable has an effect on mathematics learning outcomes students and learning discipline influence students' mathematics learning outcomes. So, it can be concluded that there is an influence of the use of gadgets and learning discipline on the mathematics learning outcomes of class VIII students at SMP Negeri 4 Samarinda for the 2023/2024 academic year.